Increased Levels of Inflammatory and Endothelial Biomarkers in Blood of Long COVID Patients Point to Thrombotic Endothelialitis - Turner, Simone; Naidoo, Caitlin A.; Usher, Thomas J.; Kruger, Arneaux; Venter, Chantelle; Laubscher, Gert J.; Khan, M Asad; Kell, Douglas B.; Pretorius, Etheresia (Seminars in Thrombosis and Hemostasis, 2023)
The prevailing hypotheses for the persistent symptoms of Long COVID have been narrowed down to immune dysregulation and autoantibodies, widespread organ damage, viral persistence, and fibrinaloid microclots (entrapping numerous inflammatory molecules) together with platelet hyperactivation. Here we demonstrate significantly increased concentrations of von Willebrand factor (VWF), platelet factor 4 (PF4), serum amyloid A (SAA), α-2 antiplasmin (α-2AP), endothelial-leukocyte adhesion molecule 1 (E-selectin), and platelet endothelial cell adhesion molecule (PECAM-1) in the soluble part of the blood. It was noteworthy that the mean level of α-2 antiplasmin exceeded the upper limit of the laboratory reference range in Long COVID patients, and the other 5 were significantly elevated in Long COVID patients as compared to the controls. This is alarming if we take into consideration that a significant amount of the total burden of these inflammatory molecules has previously been shown to be entrapped inside fibrinolysis-resistant microclots (thus decreasing the apparent level of the soluble molecules). We conclude that presence of microclotting, together with relatively high levels of six biomarkers known to be key drivers of endothelial and clotting pathology, points to thrombotic endothelialitis as a key pathological process in Long COVID.
Keywords: long COVID; von Willebrand factor; platelet factor 4; serum amyloid A; α2-antiplasmin; E-selectin; PECAM-1; thrombotic endothelialitis